Assembly and Functionality of 2D Protein Arrays - Mingming Du; Fanmeng Zeng; YueFei Wang; Ying Li; Guangcun Chen; Jiang Jiang; Qiangbin Wang (Advanced Science)
Abstract Among the unique classes of 2D nanomaterials, 2D protein arrays garner increasing attention due to their remarkable structural stability, exceptional physiochemical properties, and tunable electronic and mechanical attributes. The interest in mimicking and surpassing the precise architecture and advanced functionality of natural protein systems drives the field of 2D protein assembly toward the development of sophisticated functional materials. Recent advancements deepen the understanding of the fundamental principles governing 2D protein self‐assembly, accelerating the creation of novel functional biomaterials. These developments encompass biological, chemical, and templated strategies, facilitating the self‐organization of proteins into highly ordered and intricate 2D patterns. Consequently, these 2D protein arrays create new opportunities for integrating diverse components, from small molecules to nanoparticles, thereby enhancing the performance and versatility of materials in various applications. This review comprehensively assesses the current state of 2D protein nanotechnology, highlighting the latest methodologies for directing protein assembly into precise 2D architectures. The transformative potential of 2D protein assemblies in designing next‐generation biomaterials, particularly in areas such as biomedicine, catalysis, photosystems, and membrane filtration is also emphasized.